Behavior of Palladium Nanoparticles in the Absence or Presence of Cobalt Tetraaminophthalocyanine for the Electrooxidation of Hydrazine. Issue 5 (15th April 2014) - Maringa, Audacity; Nyokong, Tebello
Abstract We report on the electrodeposition of palladium nanoparticles (PdNPs) on a glassy carbon electrode (GCE) and onto a poly‐CoTAPc‐GCE (CoTAPc=cobalt tetraamino phthalocyanine) surface. The electrodes are denoted as PdNPs‐GCE and PdNPs/poly‐CoTAPc‐GCE, respectively. PdNPs/poly‐CoTAPc‐GCE showed the best activity for the oxidation of hydrazine at the lowest potential of −0.28 V and with the highest currents. The results were further supported by electrochemical impedance spectroscopy (EIS) which showed that there was less resistance to charge transfer for PdNPs/poly‐CoTAPc‐GCE compared to PdNPs‐GCE. The catalytic rate constant for hydrazine oxidation was 6.12×108 cm3 mol−1 s−1 using PdNPs/poly‐CoTAPc‐GCE.